Modelling General System Investment Strategy in Major Industrial and Financial Corporations - Slushaienko Nataliia V. (Bìznes Inform, 2013)
The goal of the article is the study of new qualitative approaches to development of investment strategies in major financial and industrial corporations. The article uses the games theory and methods of system analysis for modelling these processes. It considers strategies that would result in the maximal general system effect, which is the main task of the target co-ordination. The main difficulty of modelling the investment activity in major financial and production groups lies in the necessity to take into account interconnection between individual participants of the investment process and co-ordination of their interests and actions. The proposed approaches to analysis and selection of investment projects inside a major financial and industrial group facilitates making a co-ordination decision on distribution of investment resources of the general system fund and funds of individual system subdivisions. In the result of the study the article offers to use specific models of co-ordination of investment activity. These models would allow taking into consideration interaction of elements and co-ordination of interests and impact of each decision made on the state of the system. The article identifies a number of comparison criteria in the process of modelling the tasks of assessment and selection of investment projects in major financial and industrial groups. It calculates global priorities of all projects and identifies best alternatives. The proposed models could be used for assessment of interaction of elements when developing the general system investment strategy. The prospect of further studies could be identification of next approaches of optimisation of selection of the investment programme in major financial and industrial corporations.